(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2019)
The amount of drag produced significantly depends on shape of the airfoil. These implementation concerns the lift and drag analysis of three different profiles of airfoils, which are symmetrical aerofoil (NACA 0015, NACA0012) and cambered aerofoil (NACA 4415) have different volume. NACA0015 is provided with perforated tube fixed at 75% from the leading edge for suction. Electrical control system used to control the suction operation the three different types of objected has been tested at a sub-sonic wind tunnel and experimental data has been obtained at different Reynolds’s number and angle of attack. The three airfoils (symmetrical NACA 0015, NACA0012 and cambered with NACA 4415) tested at (00, 50, 100, 150 and 180) angles of attack. All the three objects tested at Re (1.72, 2.9,4, 5.2 and 6.3 x105). The cambered airfoil has been given least drag among than all the airfoils. The drag force of all test model are decreased when the value of Reynolds number are increased and NACA 4415 exhibit less drag and high lift in comparison with other models that used in this study. Suction technique is more active at lower values of Re –number.